Hempcrete as a Sustainable Building Material: A Review - Bukhari, H. (Institute of Electrical and Electronics Engineers Inc., 2021)
The construction industry needs to switch towards biodegradable environment-friendly materials so that the waste produced by this sector could be made as minimal as possible. This review deals with one such material named hempcrete which has a negative carbon footprint. The selected papers are strictly related to the use of hemp in the construction industry. Literature indicates that hempcrete offers a viable solution not only to the building sector but, if adopted rigorously, it can raise agricultural income and it suits the environment as well. It has excellent thermal, acoustic and fire-resistant features that makes it ideal for implementation. Unfortunately, the practice of using this efficient material is restricted to the western world only and even in these countries it is not readily adopted. Asia and Africa particularly lag in using this technology. It is recommended that considering the sustainable development goals, hempcrete should be given due importance to achieve maximum benefits from this energy-efficient material. In this regard, the government's assistance and sponsorship is necessary to set up plants for hempcrete manufacturing so that material can be made available to incorporate during construction. Â© 2021 IEEE.